Characterisation of electrodeposited and heat-treated Ni−Mo−P coatings - Melo,Régis L. (2012)
The electrodeposition, hardness and corrosion resistance properties of Ni−Mo−P coatings were investigated. Characterisations of the electrodeposited coatings were carried out using scanning electron microscopy, X-ray diffraction and energy dispersive X-ray analysis techniques. Corrosion tests were performed at room temperature in 10-1 mol dm-3 NaCl solutions and by potentiodynamic linear polarisation. Amorphous Ni−Mo−P coatings were successfully obtained by electrodeposition using direct current. The coating composition showed to be dependent on the bath composition, current density and bath temperature. Both P and Mo contents contribute for the hardness properties of the Ni−Mo−P coatings and the absence of cracks is a requirement to produce electrodeposited Ni−Mo−P coatings with good hardness properties. The hardness values increase with heat-treatment temperature due to the precipitation of Ni, Ni3P and NiMo phases during the heat treatment. The corrosion resistance of the electrodeposited Ni−Mo−P amorphous coatings increases with P content in the layer. Among the electrodeposited Ni−Mo−P amorphous coatings, Ni78Mo10P12 presented the best hardness and corrosion-resistance properties. The results showed that the addition of P is beneficial for the hardness and corrosion resistance properties of the Ni−Mo-based coatings.